PDRB Hijau Sektor Kehutanan Hutan Alam Kabupaten Tabalong di Provinsi Kalimantan Selatan - Icmi, Savera; Nur, Muhammad Anshar (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This study examines the influence of (1) to identify the value of depletion, forestdegradation, and depreciation Tabalong Regency in South Kalimantan Province (2)can see the value of Forestry Sector Green GRDP Tabalong Regency in SouthKalimantan Province. Data is processed using the Green GRDP calculation method.This study proves that the value of the Forestry Sector Green GRDP is smaller thanConventional GRDP. This Green GDRP shows the implementation that the TabalongRegency suffered losses due to the forest's exploitation. The result of the ForestrySector Green GRDP calculation in 2015 amount to Rp -24,413 million, in 2016,amounting to Rp. -10.816 million, and 2017 amount to Rp28,665 million.